THE IMPLEMENTATION OF AGRARIAN AND SPATIAL LAYOUT MINISTER/NATIONAL LAND AFFAIRS AGENCY HEAD’S REGULATION NUMBER 12 OF 2017 ABOUT COMPLETE SYSTEMATIC LAND REGISTRATION IN KISMOYO VILLAGE, NGEMPLAK SUB DISTRICT, BOYOLALI REGENCY - Nur Hikmah, Joko Pramono, Sri Riris Sugiyarti (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2018)
ABSTRACT  The objective of research was to analyze the Implementation of Complete Systematic Land Registration (thereafter called PSTL) Program Policy based on Agrarian and Spatial Layout Minister/National Land Affairs Agency Head’s Regulation Number 12 of 2017 in Kismoyo Village, Ngemplak Sub District, Boyolali Regency in 2017. The method employed was an empirical descriptive one with qualitative approach. The research was taken place in Kismoyo Village, Ngemplak Sub District, Boyolali Regency. The informants were selected using purposive and snowball sampling methods. Techniques of collecting data used were observation, interview, and documentation. Data validity and reliability were tested using data source triangulation technique. Technique of analyzing data used in this research was an interactive model of analysis (Miles and Huberman 1992) encompassing data collection, data reduction, data display, verification/conclusion drawing. In this research, the author referred to Van Meter and Van Horn’s arguments in which there were 6 indicators affecting the successfulness of program policy implementation: basic measures and policy objectives, policy sources, inter-organization communication, executive agency characteristic, and economic, social and political condition and implementer’s predisposition.   The result of research showed that basic measure and policy objective are good as they conform to the objective of program. This program had not met yet the need of all people who want to register their land, due to limited allocation. Human resource has been good and effective as it has involved community leader and internal institution. The Local Income and Expenditure Budget resource of Boyolali Regency had not sufficed yet all beneficiaries. Communication between organizations and implementers (executors) had been established well by National Land Affairs Agency of Boyolali Regency.  The character of implementers was good, as indicated with the commitment to catering to the people well in program implementation. Economic, social and political environment of this policy is provided to people who had no land deeds, including those coming from low and high economic level. Community participation in this program was very enthusiastic and supporting. The predisposition of implementer has good commitment to helping the implementation of Complete Systematic Land Registration (PTSL) program. Keywords: policy implementation, land registration, community